Встановлення української влади на Буковині в 1918 р. та ставлення до цього окремих етнічних груп краю. - Dobrzhanskiy, Oleksander (Wydawmictwo Naukowe, 2021)
The article analyzes the preconditions and the process of establishing Ukrainian power in Bukovyna in 1918. Particular attention is paid to the analysis of the attitude of certain ethnic groups of the region to the Ukrainian statehood. It is noted that before the division of Bukovyna along ethnic lines, Germans and Jews had a be- nevolently neutral position, the Poles and most of the Romanian politicians showed a hostile attitude.For 6 days of its existence, the Ukrainian government in Bukovina haв proven its efficiency and administrative ability. It acted as a component of the West Ukrainian People’s Republic. However, open aggression by Romania stopped the confident advance of the Ukrainians.
Keywords: Austria-Hungary, Bukovyna, West Ukrainian People’s Republic, Bukovynian Veche, Ukrainian National Rada (Council).